Environmental Economic Design of Medium Class Housing Building Models - Soliman, Mona H; El-Essawy, Mohamed A; Tantawy, Amal R (Journal of Asian Scientific Research, 2020)
This research addresses measuring the amount of produced solar energy in residential buildings and integrating and complementing them with the most appropriate design for the outer covering of housing units, and What is the amount of energy consumed and the amount of savings and rationalization required monthly and annually, So The solar thermal cooling system has been designed with absorption technique to cover the thermal loads inside the housing unit with a south-west orientation on the roof floor as the most housing unit exposed to external and internal thermal loads. Therefore, it is the most appropriate to check and test the efficiency of the performance of the absorptive solar cooling system. The highest temperature day in the summer season was chosen to read simulation results according to the climate inputs of the weather data for the city of Cairo under study with the use of the TRNSYS - simulation program. An equivalent of 83% of the monthly consumption of electricity was provided, and then an economic evaluation study was conducted for the solar thermal cooling system using the Payback Method. A system recovery period was recorded about (1.5) years and five months, and then a set of academic recommendations were reached that call for more research studies in the field of energy and sustainable environmental design.